Contributions to the sustainability professional profile - Lima, José Felipe Godoy Mello de; Pereira, Júlio César; Mergulhão, Ricardo Coser (Revista Hipótese, 2015)
Based on new thoughts about the relationship between humans and the environment, new professionals have emerged and are interested in specialising with the intention to work in organizations and to collaborate for social changing required for humanity. These changes aim to reconcile economic development and environmental responsibility. The objective of this paper is to contribute to understanding the profile of a professional in the sustainability area. A quantitative research showed the profile is directly linked to basic precepts of the sustainable development: values, changing of paradigms, environment preservation and maintenance of life quality for the present and future generations. The professionals of the sustainability area are predominantly young, female and residents of São Paulo state. They are mostly post graduates from the sustainability area and their characteristics most relevant is their expertise in sustainability and active participation in activities and projects focusing in the sustainability area.